VARIASI SAPAAN KAKANAK LALAKIAN DALAM BAHASA BANJAR - Yayuk, Rissari (Balai Bahasa Kalimantan Tengah, 2017)
This study discusses the summon variations to kakanak lalakian ‘boys’ in the Banjarese. The discussion includes how to use the summons Nang ‘Nang’, Tuh ‘See’, Atung ‘Atung’, Ucu ‘Ucu’ Busu ‘Youngest’, Pakacil ‘small Uncle’, and Tuhalus ‘whole subtle’. The research objectives is to describe the use of the summons mentioned before. It is a descriptive qualitative research. The writer conducted three steps in doing the research, namely collecting data, analysis, and presentation of data analysis. Data were collected from January to March 2016. The data was taken from a speech community in Sungai Raya, South Kalimantan. Based on the research findings, the use of certain summon is influenced by spesific reason and relation. The use of the summon Nak ‘Son’ is caused by kinship and familiarity, Nang ‘Nang’ is caused by blood relation and intimacy, Tuh ‘tuh’ is caused by kinship and familiarity.The use of the summon Atung ‘Atung’ is caused by kinship and a sense of love, Ucu ‘Ucu’ is caused by kinship, compassion, and age difference. The use Busu ‘youngest’ is caused by kinship, Pakacil ‘little uncle’ is caused by kinship, and Tuhalus ‘Whole subtle’ is caused by family relation